2011
DOI: 10.1016/j.bbamem.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the biophysical properties of GABAA ion channels: Modulation of ion permeation by drugs and protein interactions

Abstract: The fundamental properties of ion channels assure their selectivity for a particular ion, its rapid permeation through a central pore and that such electrical activity is modulated by factors that control the opening and closing (gating) of the channel. All cell types possess ion channels and their regulated flux of ions across the membrane play critical roles in all steps of life. An ion channel does not act alone to control cell excitability but rather forms part of larger protein complexes. The identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Moreover, electrophysiological recordings and kinetic analyses have shown that the long distance effects of ␥2(R43Q) substitution extend as far as the transmembrane domains (52). Therefore, ␥2(R43Q) mutation might have an influence on receptor endocytosis in line with the current views on pentameric ligand-gated ion channels, describing a link between extracellular, transmembrane, and intracellular domains (53,65,66).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 52%
“…Moreover, electrophysiological recordings and kinetic analyses have shown that the long distance effects of ␥2(R43Q) substitution extend as far as the transmembrane domains (52). Therefore, ␥2(R43Q) mutation might have an influence on receptor endocytosis in line with the current views on pentameric ligand-gated ion channels, describing a link between extracellular, transmembrane, and intracellular domains (53,65,66).…”
Section: Journal Of Biological Chemistrysupporting
confidence: 52%
“…). GABA A receptor channels show changes in sub‐state gating and single‐channel conductance when clustered rather than when dispersed at low densities, presumably through MA domain interactions between adjacent channels (Tierney, ). MS channels in embryonic stem cells show transitions between three current levels both within single activations and also as isolated events (Soria et al .…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are believed to exist in a 2:2:1 stoichiometry in vivo (McKernan and Whiting, 1996). The subunit composition determines the GABA sensitivity, the pharmacological properties of the GABA A receptor (Olsen and Sieghart, 2009) and the receptor interaction partners mediated by the larger intracellular loop between M3 and M4 (Tierney, 2011).…”
Section: Introductionmentioning
confidence: 99%